2019
DOI: 10.4136/ambi-agua.2328
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation improves physical attributes in domestic sewage effluent

Abstract: Root Zone Wastewater Treatment (RZWT) is an option of natural wastewater treatment widely studied throughout the world, being a technology based on physical, chemical and biological processes. However, there are some attributes in effluent that occasionally are not eliminated by RZWT. In this context, the use of ozone may contribute to mineralization, disinfection, detoxification, and, especially, color and turbidity removal. Ozone is an excellent oxidant, with great potential to reduce color, turbidity and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Martínez et al (2011) also found no significant results in the removal of K in a study using ozone applied in wastewater, reporting its ineffectiveness against sulfates, nitrates, potassium, and sodium. Likewise, the results obtained by Camilo Júnior et al (2019) showed great homogeneity of the mean values of K as a function of the time of exposure of ozone to the effluent and the applied doses, indicating that ozonation does not influence its value.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Martínez et al (2011) also found no significant results in the removal of K in a study using ozone applied in wastewater, reporting its ineffectiveness against sulfates, nitrates, potassium, and sodium. Likewise, the results obtained by Camilo Júnior et al (2019) showed great homogeneity of the mean values of K as a function of the time of exposure of ozone to the effluent and the applied doses, indicating that ozonation does not influence its value.…”
Section: Resultsmentioning
confidence: 86%
“…This increase in the oxygenation rate occurs both as a result of the presence of oxygen in the ozone gas and because the O3 applied to the effluent is quickly converted into O2 due to its high solubility (Camilo Júnior et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most studied components that influence the ozonation treatment are ozone dosage (Jung et al, 2017), exposure time to the gas (Camilo Júnior et al, 2019), pH value (Buffle et Ozonation as a pre-treatment of … Rev. Ambient.…”
Section: Introductionmentioning
confidence: 99%